2013
DOI: 10.3109/07357907.2013.845673
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Gleason Score and Apparent Diffusion Coefficient Obtained from Diffusion-Weighted Imaging of Prostate Cancer Patients

Abstract: The ADC values may help clinicians to delineate prostate carcinoma, recognizing its high- or low-grade compartments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The T 2 of blood is approximately 280 ms and largely independent of field strength (58). Signal fractions calculated from Equation [16] using these figures are given in Table 1. It is not simple to obtain independent estimates of ductal, stromal, and epithelial diffusion coefficients in vivo.…”
Section: Model Parametersmentioning
confidence: 99%
“…The T 2 of blood is approximately 280 ms and largely independent of field strength (58). Signal fractions calculated from Equation [16] using these figures are given in Table 1. It is not simple to obtain independent estimates of ductal, stromal, and epithelial diffusion coefficients in vivo.…”
Section: Model Parametersmentioning
confidence: 99%
“…The Gleason score acquired from biopsy or surgery on the prostate is important for the evaluation of PCa aggressiveness, selection of clinical treatment options and assessment of prognosis (6). Several studies have investigated the correlation between the apparent diffusion coefficient (ADC) value obtained from the DWI sequence and Gleason score noninvasively, however a consensus is yet to be reached on this (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…This finding was consistent with earlier studies that reported that ADC values may be useful in differentiating patients with high-or intermediate-risk prostate cancer from those with a low risk prostate cancer. 16,[23][24][25][26] In addition, several previous studies have demonstrated that high GS disease has a lower ADC value than that of low GS disease. Specifically, Nagarajan et al 17 compared ADC values with three groups of /s).…”
Section: Discussionmentioning
confidence: 99%